(untitled) (Colombia Medica, 2008)
Introduction: Sulfadoxine-pyrimethamine is an antimalarial used currently in worldwide for non-complicated falciparum malaria. This drug is administrated in combination with other ones. Previously adverse events had been reported with high doses, used in malaria prophylaxis and patients with hypersensibility to sulfas. Objetive: To evaluate hepatic and haematic toxicity of treatment with sulfadoxine-pyrimethamine (SP) in non-complicated falciparum malaria. Methodology: This was a non-blinded experimental design. In Turbo (Antioquia, Colombia), 17 subjects treated with SP were evaluated for liver and hematic function. All individual were followed for 10 days. Results: Before treatment, liver and hematic function tests were slight altedered. Hematic and liver variables returned to physiological levels after treatment. Treatment had 100% efficacy. All tests were within normal levels throughout the following period (postreatment); this suggests absence of toxic effects associates with treatment. Adverse effects were few and slight, and disappeared on day-10. Conclusions: When is used in time and dose for treatment of non-complicated falciparum malaria, SP neither increased adverse events nor hepatic or hematic toxicity.